A Note on the Preparation of Water-soluble Copper Chlorophyll - Ramachandra Rao, P.; Balaraman Naidu, P. S.; Pathak, T. C. (Indian Forester, 1956)
The preparation of water-soluble copper chlorophyll from copper chlorophyll has been described. The results of analysis of the product have been compared with those reported for a commercial sample.